The Effect of Electrolyte Type on the Li Ion Intercalation in Copper Hexacyanoferrate. Issue 10 (30th May 2019) - Gao, Caitian; Liu, Yezhou; Zheng, Lu; Feng, Erxi; Sim, Soojin; Kim, Yeongae; Yun, Jeonghun; Kim, Moobum; Lee, Seok Woo
Abstract : Copper hexacyanoferrate (CuHCFe) is proved to be a potential cathode for potassium ion and sodium ion storage in aqueous system recently. However, its ability for lithium ion storage has not been well studied. Here, we synthesized CuHCFe by a low-cost and scalable co-precipitation method, and its electrochemical behavior as the cathode for lithium ion storage was investigated both in aqueous and organic systems. The CuHCFe electrode shows larger capacity and better rate capability in organic system compared with the performance in aqueous system. In addition, the capacity has 88% retention after 500 cycles. We further analyzed the strain generated during lithium ion intercalation by ex-situ X-ray diffraction (XRD) method in both types of electrolyte. The lattice of CuHCFe shows shrinkage with ion intercalation in both systems. The measured strains are 0.70% and 0.83% in aqueous and organic system, respectively. The results indicate that the large open framework and small strain are the essential factors for the promising electrochemical performance.